2022
DOI: 10.24256/pijies.v5i1.2583
|View full text |Cite
|
Sign up to set email alerts
|

Development Of Digital Based Flash Card Media On Thematic Learning In Ibtidaiyah Madrasah

Abstract: This research is research and development. This study uses the Four D development model. The stages in the Four D development model are definition, design, development, and dissemination. However, in this study, the stages used were only up to the development stage. The subjects of this study were students of class II MIN 15 Langkat, totaling 24 people with details of 13 males and 11 females. The object of research is digital-based flashcard media. This study aims to develop digital-based flashcard media. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…From the discussion above, there are several studies that are in line with this research, including: (1) Linguist validation results with a percentage of 80.00% are categorized as appropriate. This is in line with the opinion of Novianti & Lubis (2022) which states that the validation results carried out by linguists, namely 97%, are categorized as very appropriate. Darniyanti et al (2022) said that the validation results carried out by linguists, namely 91.4%, were categorized as very appropriate.…”
Section: Discussionsupporting
confidence: 83%
“…From the discussion above, there are several studies that are in line with this research, including: (1) Linguist validation results with a percentage of 80.00% are categorized as appropriate. This is in line with the opinion of Novianti & Lubis (2022) which states that the validation results carried out by linguists, namely 97%, are categorized as very appropriate. Darniyanti et al (2022) said that the validation results carried out by linguists, namely 91.4%, were categorized as very appropriate.…”
Section: Discussionsupporting
confidence: 83%
“…Referring to some opinions and results of previous research in line with the development of Digital Flash Card media, it was found that the digital Flash Card media used in the learning process can attract the attention and interest of students so that they look active in the learning process and the learning purpose is expected to be achieved properly (Kesumawati, 2022). Furthermore, other study also mentioned that the resource-based learning model (RBL) using Flash Cards is very influential on problemsolving skills and student motivation (Koilmo, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Digital Flash Card Media can be used anywhere and anytime and can be easily accessed via mobile phone, Android, laptop, or Chromebook. Digital Flash Card Media adopts card game activities in digital form that are visualized in different and interesting ways (Fitriyani & Nulanda, 2017;Kesumawati, 2022). So that through digital flash card media, the learning process can be presented in the form of a game.…”
Section: Introductionmentioning
confidence: 99%
“…(Kesumawati et al, 2022) The formula used to calculate the percentage of digital based smart card learning media validation sheets is:…”
mentioning
confidence: 99%